Efektifitas Sanksi Pidana terhadap Pengasuh Anak karena Kelalaiannya Mengakibatkan Kematian di Taman Penitipan Anak Denpasar - Gusti Ayu Putri Pratiwi; I Made Sepud; Diah Gayatri Sudibya (Jurnal Konstruksi Hukum, 2020)
The rapid development of science and technology has led to many cases of criminal acts against children in the field of educational services. There are various kinds of crimes against human rights violations in the field of child protection, one of which is negligence in caring for and educating children. This study aims to determine the factors that cause death in foster children in TPA Princess House Childcare and to determine the effectiveness of criminal sanctions against child caregivers who due to their negligence cause death in children. The research method uses empirical research type. The statutory approach is to examine all laws and regulations related to the legal issue being researched, and to use a case approach. Sources of data obtained through informants with direct field interviews are then processed and analyzed descriptively. The results showed that negligence that resulted in death could occur through two factors, namely external factors and internal factors. Regarding the sanctions against the perpetrator who resulted in the loss of a child's life, it is felt that it has been effective and implemented in accordance with the provisions as stipulated in Article 76B in conjunction with Article 77B of the Law of the Republic of Indonesia Number 35 of 2014, imprisoned for 3 (three) years and a fine as much as RP. 50,000,000,-